Mechanism of Brønsted acid-catalyzed conversion of carbohydrates - Yang, Gang; Pidko, Evgeny A.; Hensen, Emiel J.M. (Journal of catalysis, 2012)
Potential Brønsted acid-catalyzed glucose and fructose conversion routes to levulinic acid have been studied by DFT calculations. The most favorable mechanisms for sugar transformations initiated by protonation of different OH groups are identified. It is demonstrated that the differences in the reactivity of glucose and fructose in acidic aqueous solutions are dominated by the regioselectivity of the initial protonation step. [Display omitted] ► Regioselectivity of the initial protonation of sugars determines selectivity of their conversion. ► Favorable protonation of fructose opens path to levulinic acid via HMF intermediate. ► Favorable protonation of glucose leads to reversion products and humin precursors. ► Novel direct mechanism of glucose transformation to levulinic acid is reported. A comprehensive DFT study of acid-catalyzed glucose and fructose reactions in water covering more than 100 potential reaction paths is performed with the aim to identify the main reaction channels for obtaining such desirable biorefinery platform products as 5-hydroxymethylfurfural (HMF) and levulinic acid (LA). Characteristic for fructose dehydration by Brønsted acids is the preferred protonation of the O2H group at the anomeric carbon atom, which initiates a sequence of facile reactions toward HMF. Further rehydration to LA is more difficult and competes with condensation reactions leading to humins. A very different result is obtained when glucose is the reactant. The preferred protonation site is the O1H hydroxyl group. The associated reaction paths do not lead to the formation of HMF or LA but result in humin precursors and reversion products. Protonation of other sites occurs at a much lower rate. Nevertheless, when glucose is activated at these less reactive sites, it can lead to LA via a reaction mechanism that does not involve the intermediate formation of fructose and HMF. This direct mechanism is argued to be preferred over the conventional sequential conversion scheme. It is concluded that the differences in the reactivity of glucose and fructose in acidic aqueous solutions are dominated by the regioselectivity of the initial protonation step.